ANGKA KEBERHASILAN TERAPI EKSISI DAN RADIOTERAPI ADJUVAN PADA PASIEN KELOID YANG DIOPERASI DI RUMAH SAKIT UNAND - Iffah Annadiyah; Fory Fortuna; Hendriati (JURNAL KESEHATAN INDRA HUSADA, 2025)
Keloid is a benign fibroproliferative tumor of the dermal that extends beyond the original wound and invades adjacent dermal tissue due to an abnormal healing response from the wound in the dermis. Keloids can have a disturbing impact on individuals such as cosmetic disorders, pruritus, pain, and in severe cases, limited joint movement so that it is very necessary to be managed. One of the keloid therapies with quite promising results is surgical excision and adjuvant radiotherapy. This aim of this research was to determine the success rate of excision therapy and adjuvant radiotherapy in keloid patients operated on at Unand Hospital. This research is an observational descriptive study and uses a cross- sectional design using a total sampling technique of 12 samples. Data analysis uses univariate analysis and research data is presented in the form of a table of success rates. The Results In this study, the highest success rate was found in the 12-16 year age group, female gender, lower extremity predilection. All patients received external radiation with the highest success rate in the group of patients who were given a total dose of 20 Gy in 5 fractions, a follow-up interval of 6 months, and a distance of excision and adjuvant radiotherapy for <3x24 hours, and adhered to the fixed therapy protocol. The success of therapy is largely influenced by predilection, age, gender, radiation dose, and patient compliance with therapy.